Performance evaluation of a new fourth-generation HIV Ag/Ab combination electrochemiluminescence immunoassay – evaluation of a new HIV assay. (March 2014) - Wang, Tingting; Li, Dongdong; Yan, Kening; Yuan, Yu; Yang, Tingfu; Du, Xiaoqing; Yan, Xuedan; Tao, Chuanmin; Wang, Lanlan
A new fourth-generation HIV Ag/Ab electrochemiluminescence immunoassay for screening of HIV infection, the Elecsys® HIV Combi PT (Roche Diagnostics, Penzberg, Germany) assay, is going to be commercially available in clinical laboratories in China. This assay was evaluated and compared with two commonly used assays: Elecsys® HIV Combi assay and the Livzon anti-HIV-1/2 ELISA. Commercially available panels and 30 established HIV infection samples were tested to evaluate the sensitivity. In addition, a total of 675 routine clinical samples were collected and tested in West China Hospital to compare the specificity. Any reactive result from a screening test was retested and all reactive retested samples were confirmed with Western blot assay, Elecsys® HIV Ag test, Elecsys® HIV Ag confirmatory test or HIV-1 RNA NAT testing. According to the results of the HIV seroconversion panels, the Elecsys® HIV Combi PT could detect seroconversion at the same bleed or at least one bleed earlier compared to the other two assays. Among the 675 clinical samples, most results were consistent except for one specimen with a false-negative result using Elecsys® HIV Combi assay. In conclusion, the Elecsys® HIV Combi PT has shown satisfactory sensitivity and specificity to be a screening test for HIV infection.